Percutaneous nephrolithotomy: the puncture : review - Alken, Peter (BJU international, 2022)
Objective To determine what importance is given to the puncture and assistive technologies in percutaneous nephrolithotomy (PNL) in the current urological literature. Methods PubMed was searched for English publications and reviews for the keywords: ‘percutaneous nephrolithotomy’, ‘percutaneous nephrostomy’, ‘puncture’. The search was limited to the last 5 years, January 2016 until February 2021. Based on 183 abstracts, 121 publications were selected, read, and reviewed. References, older or seminal papers were read and cited if they contributed to a better understanding. A total of 198 references form the basis of this narrative review. Results The puncture is frequently referred to as the most crucial part of PNL. In contrast, the influence of the puncture on the failure rate of PNL and the specific puncture-related complications seems to be low in the single-digit percentage range. However, there are no universally accepted definitions and standards measuring the quality of puncture. Consequently, the impact of the puncture on general PNL complications, on stone scores predicting success rates and on learning curves evaluating surgeons’ performance have not been systematically studied. Assistive technologies rely on fluoroscopy and ultrasonography, the latter of which is becoming the preferred imaging modality for monitoring the entire procedure. Needle bending, a problem relevant to all puncture techniques, is not addressed in the urological literature. Conclusions The importance attached to puncture in PNL in the current urological literature is subjectively high but objectively low. Some basics of puncture are not well understood in urology. Disciplines other than urology are more actively involved in the development of puncture techniques.
First published: 08 August 2021
Gesehen am 29.11.2022